1980
DOI: 10.1177/016001768000500203
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Accuracy in Regional Input-Output Models

Abstract: This paper focuses attention on the concept of accuracy in regional input-output tables. Two interpretations of accuracy, namely partitive and holistic accuracy, are discussed with reference to interpretation of input-output tables. Implications are drawn from recent contributions to the regional input-output literature in terms of the `reconciliation' debate and the survey versus non-survey debate. Holistic accuracy is the only concept which is tenable in practice; some suggested criteria for holistic accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
10

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 12 publications
0
55
0
10
Order By: Relevance
“…Thus, for these results to be confirmed, more detailed uncertainty data, including correlations, is needed. In addition, since it is also found that the most uncertain data are usually small and have only little impact on the results (Lenzen et al, 2010;Jensen, 1980;Jensen and West, 1980), then it may be more effective to perform targeted sensitivity analysis (Wilting, 2012). Nevertheless, the available literature suggests the variation in economic data may not be that important for consumption-based estimates at the national level, but differences may persist at the sector level (Lenzen et al, 2010;Lenzen, 2011;Wilting, 2012).…”
Section: G P Peters Et Al: a Synthesis Of Carbon In International mentioning
confidence: 99%
“…Thus, for these results to be confirmed, more detailed uncertainty data, including correlations, is needed. In addition, since it is also found that the most uncertain data are usually small and have only little impact on the results (Lenzen et al, 2010;Jensen, 1980;Jensen and West, 1980), then it may be more effective to perform targeted sensitivity analysis (Wilting, 2012). Nevertheless, the available literature suggests the variation in economic data may not be that important for consumption-based estimates at the national level, but differences may persist at the sector level (Lenzen et al, 2010;Lenzen, 2011;Wilting, 2012).…”
Section: G P Peters Et Al: a Synthesis Of Carbon In International mentioning
confidence: 99%
“…Clearly, there are benefits in avoiding, where possible, the processing and storing of mathematical manipulations that do not improve the overall accuracy of the model (see Jensen, 1980 for a discussion on these points).…”
Section: Transparency In Data Processingmentioning
confidence: 99%
“…Thus validation is not a test that is reported but a practice where researchers examine and state the degree of validity of the model in question (Jensen 1991). In the process of compiling inputoutput tables errors may be introduced due to factors such as interregional variations in prices, consumption patterns, inter-regional trade relationships, and spatial variations in technology among others (Jackson 2001 Jensen (1980) distinguishes between these two terms in the context of deriving synthetic tables. A partitive accuracy focuses on cell by cell precision in a statistical sense within inputoutput tables, while holistic accuracy centers on identifying the main features of the economy in a descriptive sense and preserves the importance of these features in an analytical sense.…”
Section: Verification and Validationmentioning
confidence: 99%
“…A partitive accuracy focuses on cell by cell precision in a statistical sense within inputoutput tables, while holistic accuracy centers on identifying the main features of the economy in a descriptive sense and preserves the importance of these features in an analytical sense. Also, partitive accuracy maintains that the table will be holistically accurate; but holistic accuracy does not guarantee a high degree of partitive accuracy (Jensen 1980 Table 8. The results are based upon implementing the tiered approach for identifying the fundamental economic structure and the associated fundamental economic structure characteristics.…”
Section: Verification and Validationmentioning
confidence: 99%